(untitled) (American Journal of Islam and Society, 2016)
On October 15, 2105, the International Institute of Islamic Thought commemorated Ali Mazrui’s (1933- 2014) first death anniversary by convening a seminar to honor their mutual close and lasting relationship. Mazrui served as the editor-in-chief of the American Journal of Islamic Social Sciences (2009-14), participated in many of the institute’s events, and was awarded the IIIT Distinguished Scholar Award in 2011. In addition, he bequeathed his collection of papers and publications to IIIT. His widow Pauline Utimazrui opened the seminar by recalling how her late husband always spoke the truth regardless of the consequences, how he decided to attend Columbia University because so many African students were going there, and how he sought to bring up controversial issues to force people to think outside the box. She said that he was a very happy and grateful man who appreciated others, liked to live a simple life and be in the moment, and did not believe in accumulating wealth. Keynote speaker Ebrahim Rasool, former ambassador of South Africa to the United States and a long-time activist who was jailed for his anti-apartheid activities, spoke on “Ali Mazrui: Beacon at the Intersection of Islam and Africa.” He described Mazrui as follows: Standing for justice is the point of the triangle which is least populated, or if it is populated it may well be populated in the absence of understanding the implications of belief in the unity of God or the understanding of the dynamism of knowledge. Professor Ali Mazrui will be remembered for epitomizing the completeness and perfection of this golden triangle [of belief, knowledge and justice], for indeed his knowledge was founded in his unflinching commitment to Tauhid or unity and this, in turn, impelled him towards utilizing his intellect both towards identifying the sources of injustice in the world and positing theoretical and practical solutions towards justice. He reminded his audience how Mazrui never shied away from controversy, as can be seen in his battle with National Public Radio (NPR) in terms of his production and defense of “The Africans: The Triple Heritage,” disagreements with much of post-colonial Africa’s ideological or philosophical thinking, and assertion of a distinction between theological Islam and historical Islam. On a more personal level, in 1969 he rejected an invitation extended ...